Internationalization MSMEs Export Challenge: Case Study on Kopi Dampit East Java, Indonesia - Risca Kurnia Sari; Sudarmiatin; Rozmiza Bidin; Satria Putra Utama (PT FORMOSA CENDEKIA GLOBAL, 2024)
The objectives of this study are to explore the experiences of MSMEs towards internationalization, Identify the main barriers of MSMEs in entering international markets, and What are the barriers that cannot be overcome by MSMEs, forcing MSMEs to choose to de-internationalize international markets? Case study research was conducted in this study, This research carried out in February 2024. The method used is a qualitative method with descriptive analytical, verification and explanatory approaches. The results of the research conducted can be concluded that to make efforts to internationalize small businesses need to pay attention to the challenges and factors that become obstacles in its implementation. The study contributes significantly knowing what aspects cause failure in the internationalization of MSMEs because this can be improved so that it can be maximized in the future and can contribute to encouraging MSMEs to go to the next level.